PERANAN AKUNTAN PUBLIK ATAS KEPATUHAN PAJAK (Media Riset Akuntansi, 2022)
This study aims to analyze the role of the Public Accountant related to Tax Compliance and analyze the strategies used by the Tax Office of the Big Taxpayer II to manage the compliance of the registered Big Taxpayer. The research method used is descriptive qualitative data collection techniques in the form of content analysis. This study uses secondary data published by Indonesian state government agencies that formulate and implement tax compliance, namely the Directorate General of Taxes. The results of this study indicate that Public Accountants play an important role in increasing tax compliance from taxpayers; Large Taxpayer Service Office II implements all the strategies that have been formulated in managing tax compliance from taxpayers; and the strategy implemented by the Large Taxpayer Service Office II has a quite positive impact on taxpayers in the territory of the Large Taxpayer II.